Formulation of an assessment tool on basic service-level standards for resettlement projects - Marife Magno-Ballesteros; Amillah S. Rodil; Tatum P. Ramos; Pauline Joy M. Lorenzo; Jenica A. Ancheta (Philippine Institute for Development Studies (PIDS), 2024)
The Philippine government has promoted and institutionalized the delivery of basic services in resettlement sites through various flagship housing programs and the issuance of policies, guidelines, and/or standards. Existing literature suggests, however, that most resettlement sites lack the basic services and the social and economic opportunities to ensure the development of liveable and sustainable communities. The study notes that resettlement projects must be carefully planned in terms of both the processes and the physical design. Government laws and policies must be translated into clear minimum standards that are adopted at the national and subnational level. To formulate these standards, the authors reviewed existing local and international policies and guidelines on resettlement housing and examined the good practices in selected resettlement projects and among project implementers. The policy mapping and case study led to the identification of policy and implementation gaps, which were used in the development and refinement of the assessment tool for resettlement planning.
Keywords: 330; social housing; resettlement projects; settlement planning; resettlement standards